Impact of fiducial markers placement on the delineation of target volumes in radiation therapy for oesophageal cancer: FIDUCOR study - Rochigneux, Philippe; Tyran, Marguerite; Autret, Aurélie; Lopez Almeida, Leonor; Guiramand, Jérôme; Ferre, Marjorie; Chanez, Brice; Mitry, Emmanuel; Ratone, Jean Philippe; Giovannini, Marc; Tallet, Agnès; Moureau-Zabotto, Laurence; et al. (Frontiers in Oncology, 2022)
Purpose This prospective monocentric phase II study (FIDUCOR-study, NCT02526134) aimed to assess the impact of fiducial markers (FMs) implantation on conformal chemo-radiation therapy (CRT) planning in oesophageal carcinoma (EC) patients. Methods/materials Fifteen EC patients were enrolled in the study. Each patient underwent two simulation CT-scans before (CT1) and after (CT2) FMs implantation, in the same position. FMs (3 mm length gold markers, preloaded in a 22G needle) were implanted after sedation, under endoscopic ultrasound (EUS) and X-Ray guidance, and were placed at the tumor’s extremities, and in the visible lymph nodes. Target delineation and treatment plan were both performed first on CT1 with the assistance of diagnosis CT, gastroscopy and EUS details, and second on CT2 using FMs and CT-data. The value of FMs implantation was assessed by the difference of growth-tumor-volume (GTV) and clinical-target-volume (CTV) between CT1-based and CT2-based delineation. A significant difference was defined as a ≥5 mm-difference on axial(x) or coronal(y) slices, a ≥10mm-difference on sagittal slices, or a ≥20%-difference in GTV. The impact on dose distribution in organs at risk (OAR) (lung, heart, liver) was also studied. Results Between 09/2014 and 12/2015, 15 patients could achieve fiducial procedures, without any complication. One FM migration occurred. We observed a significant modification of the GTV-dimension in 100% of the cases (15/15, 95%CI: [78.2;100.0]), mainly due to a difference in sagittal dimension with a mean variation of 11.2 mm and a difference> 10 mm for 8/15 patients (53.3%). One patient had a significant isocenter displacement as high as 20 mm. The oesophagus tumor was not seen on the CT-scan in one patient due to its small size. One patient had a distant lymph node metastasis not visible on CT-scan. We observed no significant impact on OAR distribution. Conclusion In our study, FMs-implantation under EUS had a positive impact on accurate volume definition in EC-patients (modification of GTV in 15/15 patients). Close cooperation between gastroenterologist and radiation oncologist has the potential to improve local treatment of oesophageal carcinoma.